2013
DOI: 10.1016/j.jaci.2013.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency is associated with challenge-proven food allergy in infants

Abstract: These results provide the first direct evidence that vitamin D sufficiency may be an important protective factor for food allergy in the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
2
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(201 citation statements)
references
References 30 publications
7
178
2
10
Order By: Relevance
“…Since then, a considerable number of studies had been conducted linking vitamin D deficiency with autoimmune diseases and allergic disorders (Munger et al 2006;Frieri & Valluri 2011;Allen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a considerable number of studies had been conducted linking vitamin D deficiency with autoimmune diseases and allergic disorders (Munger et al 2006;Frieri & Valluri 2011;Allen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial (n = 180) found that vitamin D supplementation during late pregnancy had no effect on the occurrence of wheezing, atopy, eczema or food allergy in the child by the age of 3 years [12]. Cross-sectional studies on children have either reported inverse associations with 25-OHD serum levels and atopic dermatitis [13] or food allergy [14], or no association [15]. …”
Section: Introductionmentioning
confidence: 99%
“…137,138,139,140 Omega 3 El suplemento en el embarazo y la LM requiere mayor evidencia. 141 Cesárea Potenciaría el desarrollo de AA en niños predispuestos, por desregular la microbiota.…”
Section: Tabla 12 Medidas Preventivas Aspectos Relevantesunclassified